Stratigraphic evidence for an early Holocene earthquake in Aceh, Indonesia - Grand Pre, C.; Horton, B. P.; Kelsey, H. M.; Rubin, C. M.; Hawkes, A. D.; Daryono, M.; Rosenberg, G.; Culver, S. J. (Quaternary Science Reviews, 2012)
The Holocene stratigraphy of the coastal plain of the Aceh Province of Sumatra contains 6 m of sediment with three regionally consistent buried soils above pre-Quaternary bedrock or pre-Holocene unconsolidated sediment. Litho-, bio-, and chronostratigraphic analyses of the lower buried soil reveals a rapid change in relative sea-level caused by coseismic subsidence during an earlyHolocene megathrust earthquake. Evidence for paleoseismic subsidence is preserved as a buried mangrove soil, dominated by a pollen assemblage of Rhizophora and/or Bruguiera/Ceriops taxa. The soil is abruptly overlain by a thin tsunami sand. The sand contains mixed pollen and abraded foraminiferal assemblages of both offshore and onshore environments. The tsunami sand grades upward into mud that contains both well-preserved foraminifera of intertidal origin and individuals of the gastropod Cerithidea cingulata. Radiocarbon ages from the pre- and post-seismic sedimentary sequences constrain the paleoearthquake to 6500–7000 cal. yrs. BP. We use micro-and macrofossil data to determine the local paleoenvironment before and after the earthquake. We estimate coseismic subsidence to be 0.45 ± 0.30 m, which is comparable to the 0.6 m of subsidence observed during the 2004 Aceh–Andaman earthquake on Aceh’s west coast.
id: 2139